PROTECTION OF PATIENT RIGHTS IN HOSPITALS: A LITERATURE REVIEW ON THE IMPLEMENTATION OF LAW NO. 44 OF 2009 ON HOSPITALS - Gunawan Widjaja (RADJA PUBLIKA, 2025)
This study aims to examine the implementation of patient rights protection in hospitals based on Law No. 44 of 2009 concerning Hospitals through a literature review. The results of the study indicate that, normatively, this law has provided a strong legal basis for the fulfilment of patient rights, such as the right to information, privacy, quality service, and the right to file complaints. However, implementation in the field still faces various obstacles, including low patient awareness of their rights, lack of socialisation from hospitals, and suboptimal complaint mechanisms and law enforcement against violations of patient rights. Efforts made by hospitals include education, the provision of complaint facilities, and the application of service standards, but strengthening is still needed in the areas of socialisation, transparency, and supervision so that the protection of patient rights can be realised effectively and evenly. This study recommends the need for collaboration between various parties, increased human resource capacity, and reformulation of regulations to strengthen access to justice for patients.